INFRARED THERMOGRAPHY TO MAP THE UDDER HEALTH STATUS OF ZEBUINE DAIRY COWS - Celia Raquel Quirino; Júlia Gazzoni Jardim; Lucas Milagres Nogueira; Araceli Rocio Marisel González; Aparecida Fátima Madella- Oliveira (Tropical and Subtropical Agroecosystems, 2021)
Background: Infrared thermography is a diagnostic imaging technique that detects the emission of heat by infrared radiation, indicating the temperature of a particular area. Objective: The objective of this study was to measure the magnitude of the udder temperature variation by infrared thermography for mastitis diagnosis of zebuine dairy cows in a tropical pasture-based system. Methodology: The udder temperature of Holstein-Gyr crossbred cows was measured with a FLIR® camera. Milk samples were collected for CMT and somatic cell count determination. The surface temperature of the mammary gland and rectal temperature were grouped according to udder health status of animals and were submitted to analysis of variance and correlation analysis. Results: The udder temperatures were higher for the clinical mastitis group (37.2±0.7 °C) than the subclinical mastitis (36.6±0.9 °C) and healthy udder (36.3 ±1.0 °C) groups. A weak positive correlation (r=0.18) was observed between somatic cell count (SCC) and udder temperature. A strong positive correlation (r=0.68) was observed between rectal temperature and udder temperature. Implications: The results of this work can be applied in the future in precision animal husbandry, generating more efficient strategies and practices for the diagnosis and control of mastitis, since it is a promising tool for easy and quick diagnosis of mastitis. Conclusions: Infrared thermography can be an effective method for diagnosing mastitis in cows. However, its use should be made with the complementary California mastitis test.